Juvenile Registration and Notification Policies Fail to Prevent First-Time Sexual Offenses: An Extension of Findings to Two New States - Letourneau, Elizabeth J. (Criminal justice policy review, 2019)
This study evaluated the effects of Maryland and Oregon juvenile sex offender registration and notification policies on first-time sexual offense charges and adjudications. We used autoregressive modeling to compare the monthly average of first-time sexual offense charges (N = 5,657 and 13,278 for Maryland and Oregon, respectively) and adjudications (N = 1,631 and 5,451 for Maryland and Oregon, respectively) across pre- and post-policy years. Results indicate that neither state’s registration policy had any impact on first-time sexual offense charges or adjudications and are consistent with prior studies evaluating the juvenile registration and notification policies of four other states. The absence of general deterrence effects across three studies evaluating six state registration policies suggests that, regardless of specific policy characteristics, juvenile registration and notification policies fail to improve community safety via deterring first-time sexual offenses among children. Recommendations include replacing juvenile registration policies with more effective prevention and intervention practices.